Tinjauan Yuridis Penyelesaian Sengketa Terhadap Pengalihan Tanah Wakaf Sebagai Fasilitas Umum - Chandra Munthe; Jamilah Jamilah; Abdul Lawali Hasibuan (Universitas Medan Area, 2020)
According to Islamic law, various views of some schools forbid changing or transferring waqf property, while some other schools allow that the assets cannot be taken advantage of or reduced in benefits and must be replaced. Meanwhile, according to legal regulations in Indonesia and the Compilation of Islamic Law allow with certain conditions. This study uses descriptive research and the nature of the research used is included in the category of normative legal research. Legal arrangements regarding the transfer of waqf land in Indonesia are regulated in Presidential Instruction No. RI. 1 of 1991 concerning Compilation of Islamic Law in Article 225 paragraphs (1) and (2), Article 49 paragraph (1) of Law Number 41 of 2004 concerning Endowments, Article 49 paragraph (2) Government Regulation No. 25 of 2018 concerning the Implementation of Law No. 41 of 2004 concerning Endowments. Management of waqf land namely Nazir makes a letter of application for submission of waqf land for public facilities to the Minister of Religion by attaching the certificate of waqf pledge certificate, certificate of proof of ownership of the substitute land for waqf, Tax Object Sales Value (NJOP) of waqf land and its exchanges, spatial plans from local government, and other letters. The resolution of the waqf land dispute is carried out through three stages, namely through deliberation efforts to obtain consensus, mediation, and legal efforts to file a claim to the Religious Court.